The Correlation between Myelucleopidase Levels and the Event of the Acute Coronary Syndrome (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Acute coronary syndrome (ACS) is a collection of symptoms due to cardiac blood flowdisorders consisting of acute myocardial infarction (AMI) with increased ST segment (STEMI), AMIwithout increased ST segment (NSTEMI) and unstable angina pectoris (UA). Myeloperoxidase (MPO) isan enzyme that plays a role in the destabilization and rupture of plaque that rises earlier within 2 hoursafter AMI attack so it can be used as an early marker of ACS without depending on evidence of myocardialnecrosis. So, the purpose of this study is to determine the relationship between MPO levels and ACS events.Methods: This study is using quantitative method. Research sample was 40 patients serum with the maincomplaint of chest pain that fulfilled the inclusion criteria who came to the emergency unit of Dr.SoetomoGeneral Hospital Surabaya. The blood samples were examined for MPO with MPO kit from Quanticine (R& D system) using ELISA method. The diagnostic value obtained from the calculation with the 2x2 table.Results: Patients with chest pain were 27 persons (67.5%), while non-ACS patients were 13 persons(32.5%). There were significant differences in MPO levels between the STA (STEMI, NSTEMI, UA) groupsof 986.48 ng/ml and non-ACS 381.08 ng/ml (p = 0.002). Diagnostic sensitivity was 88.88%, diagnosticspecificity 69.23%, negative predictive value 75% and positive predictive value 85.71%. The correlationcoefficient between MPO and ACS content is r = 0.45 with p = 0.003.Conclusion: There was a correlation between MPO levels and the incidence of ACS. The higher the MPOlevel the higher the incidence of ACS.
Keywords: sindroma coroner, infark miokard akut, unstable angina, nekrosis miokard.